FAKTOR – FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN - SELVI SEMBIRING; ITA TRISNAWATI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
The purpose of this research is to obtain the empirical evidence about factors which influence firm value. The independent variabels in this research are manajerial ownership, institutional ownership, capital structure, profitability, company growth, firm size, dividen policy and the dependent variable is firm value. Population in this research are manufacturing companies listed in Indonesian Stock Exchange from 2013 – 2016. And period of this research is 2014 – 2016. The selection of samples used purposive sampling method and there are 42 companies and 123 observations meet those criteria for samples. This research uses multiple regression method for data analysis. The result of this research shows that capital structure, profitability, company growth and firm size have influence to firm value. Where as, manajerial ownership, institutional ownership and dividen policy have not influence to firm value.